Pertimbangan Hakim Terhadap Tindak Pidana Pencurian Dengan Pemberatan Yang Dilakukan Oleh Anak (Studi Kasus Putusan Pidana Nomor: 01/Pid.Sus.Anak/2015/PN.Krg) - Septia Valentina, Ellyvia; , Hartanto,SH, M.Hum (2017)
This study aims to determine consideration of the judge in imposing punishment on criminal acts of theft by weighting done by children as well as knowing the constraints of judges in imposing punishment on criminal acts of theft by weighting done by children in Karanganyar. The method used is the juridical-normative with descriptive qualitative analysis. The results showed that the consideration of the judge in the verdict has fulfilled all of the elements of the offense and terms of the imposition of punishment against the defendant and has been proven legally and convincingly of committing criminal offenses of theft by weighting as stipulated in Article 363 paragraph (1) 3rd and 5th Penal Code jo Law No. 11 Year 2012 on Child Criminal Justice System. The constraints faced by the judge in imposing punishment on criminal acts of theft by weighting done by children in the District Court Karanganyar that children's knowledge on legal issues is still limited, the fear to face the law, the absence of a dedicated space and specialized cells that comfortable, and the absence parent / guardian at the hearing.